PENGEMBANGAN MEDIA GAMBAR BERSERI BERBASIS POP-UP BOOK UNTUK MENINGKATKAN KEMAMPUAN BERBICARA KELAS II SEKOLAH DASAR - Andara Sintho Retnoningtya; Alfi Laila; Rian Damariswara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research and development is to determine the level of validity, practicality and effectiveness of pop-up book-based serial picture learning media to improve speaking skills in class II elementary schools. The research method used is R & D (Research and Development) with the ADDIE model which consists of 5 steps, namely (1) Analysis, (2) Design (design), (3) Development (development), (4) Implementation (implementation) , (5) Evaluation (Evaluation). The results of this research show that. (1) The validation results obtained from the media validator reached a percentage of 96% and the material validator reached 88%, so the validation results are included in the very valid criteria. (2) The results of the limited scale teacher response questionnaire were 96%, the broad scale teacher response was 94% and the results of the limited scale student response questionnaire were 98%, the results of the broad scale student questionnaire were 97%, reaching very good criteria, so the practicality of pop-up book-based serial picture learning media wisdom has very practical criteria. (3) the results of the effectiveness test on a limited scale obtain a normality test value of sig. of 0.942 > 0.005 and 0.499 > 0.05, the data is normally distributed, on a broad scale the normality test results get a value of 0.136 > 0.05 and 0.291 > 0.05, the data is normally distributed, the homogeneity test gets a value of 0.053 > 0.05, so the data is the same or homogeneous, the t-test gets a sig value. (2-tailed) obtained is 0.000 < 0.05, so there is a difference between the post-test and pre-test, which means there is an influence of the use of pop up book serial image learning media on improving student learning.